Bentuk ~You To Suru Dalam Kalimat Bahasa Jepang - Elizabeth Ika Hesti Aprilia Nindia Rini (KIRYOKU, 2019)
-You to suru form has two functions, i.e. as a marker of interpersonal modality and a marker of incoative aspects. This study aims to describe the structure and meaning of -you to suru form in order to use it in the right situation. The method used in this study is agih method, and bagi unsur langsung techniques. As a result of the research, it was found that -you to suru form as a marker of intention modality stated effort in doing something; and as a marker of the incoative aspect stated  the start of an activity. As a marker of intention modality, the form of -you to suru is attached to volitional verbs; while as a marker of the incoative aspect, -you to suru form is attached to both volitional and non volitional verbs.